Analisis Kepuasan Kerja Karyawan Fakultas Ekonomi Universitas Sriwijaya Berdasarkan Karakteristik Individu - Wita Farla (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2016)
The purpose of this study was to determine whether there are differences in employee satisfaction when seen from the characteristics of the individual, which consists of age, gender, marital status, length of work, education, and employment status. The sampling technique used is Saturated Samples where the entire population sampled. Data was analyzed using frequency analysis, cross tabulation and chi-square. The findings in this study were mostly employees have been satisfied with the work; there is no difference in job satisfaction of employees based on age, gender, length of work, education, and employment status. Instead there is difference in employee satisfaction when seen from her marital status